MiR‐205 promotes endothelial progenitor cell angiogenesis and deep vein thrombosis recanalization and resolution by targeting PTEN to regulate Akt/autophagy pathway and MMP2 expression - Sun, Li‐Li; Xiao, Lun; Du, Xiao‐Long; Hong, Lei; Li, Cheng‐Long; Jiao, Jian; Li, Wen‐Dong; Li, Xiao‐Qiang (Journal of cellular and molecular medicine, 2019)
MicroRNAs (MiRNAs, MiRs) represent a class of conserved small non‐coding RNAs that affect post‐transcriptional gene regulation and play a vital role in angiogenesis, proliferation, apoptosis, migration and invasion. They are essential for a wide range of physiological and pathological processes, especially for vascular diseases. However, data concerning miRNAs in endothelial progenitor cells (EPCs) and deep vein thrombosis (DVT) remain incomplete. We explored miRNAs that modulate angiogenesis in EPCs and thrombolysis, and analysed their underlying mechanisms using a DVT model, dual‐luciferase reporter assay, qRT‐PCR, Western blot, immunofluorescence staining, flow cytometry analysis, CCK‐8 assay, angiogenesis assay, wound healing and Transwell assay. We found that miR‐205 enhanced the homing ability of EPCs to DVT sites and promoted thrombosis resolution and recanalization, which significantly reduced venous thrombus. Additionally, we demonstrated that miR‐205 overexpression significantly enhanced angiogenesis in vivo and in vitro, migration, invasion, F‐actin filaments and proliferation in EPCs, and inhibited cell apoptosis. Conversely, down‐regulation of miR‐205 played the opposite role in EPCs. Importantly, this study demonstrated that miR‐205 directly targeted PTEN to modulate the Akt/autophagy pathway and MMP2 expression, subsequently playing a key role in EPC function and DVT recanalization and resolution. These results elucidated the pro‐angiogenesis effects of miR‐205 in EPCs and established it as a potential target for DVT treatment.